Identifikasi Jenis Mineral Magnetik Berdasarkan Uji XRF pada Sedimen Permukaan Sungai Bone di Daerah Pertambangan di DesaTulabolo Timur, Suwawa, Kabupaten Gorontalo - Nono’o, Sandra; Yunginger, Raghel; Tamuntuan, Gerald H; Demulawa, Meilan; Supu, Idawati (Universitas Lambung Mangkurat, 2023)
This study aims to determine the Types of Magnetic Minerals in Bone River Sediments in the Mining Area of Tulabolo Village. The XRF test was used to identify Magnetic Mineral elements in Bone River Sediments, and electrical conductivity (EC), pH, and temperature parameters for in situ measurements of Bone River water samples and measures of mineral types was carried out on prepared sediment samples. The results showed that direct measurements on water samples showed that the values of EC, pH, and temperature were (1,620-1,900) µS/cm, (5-7), and (25.0-25.9)oC, respectively. While the results of measurements using XRF elements that have the most significant percentage are elements (Si), especially at the S10 point of 58.84% diamagnetic minerals, elements (Fe), especially at the S7 point of 22.80%, element (Al) at the S10 point of 8, 11%, elements (Ti) at point S1 1.84% which are ferromagnetic minerals. Elements (Ca) at end S2 of (2.67%), elements (K) at point S1 of 1.50% paramagnetic minerals.